Focused ion beam machining of silicon - Hung, NguyenPhu; Fu, Yongqi; Ali, Mohammad Yeakub (Elsevier BV, 2002)
This paper optimizes the parameters of a focused gallium ion beam system for the micromachining of single-crystal silicon. The effect of the parameters on the surface integrity and material removal rate (MRR) were studied. The surface integrity and machined features were measured with a scanning probe microscope. Statistical models were established to predict the sputtered depths and MRRs. The sputtering depth increased with higher accelerating voltage, more ion dose, shorter pixel spacing, and longer dwell time. Similar trends were found for predicting the MRR. A surface roughness in the range of 2-5 nm was achieved, and was found to be linearly dependent on the pixel spacing. © 2002 Elsevier Science B.V. All rights reserved.